Investigating the Management of Carious Primary Teeth in General Dental Practice: An Overview of the Development and Conduct of the Fiction Trial. Issue 4 (December 2015) - Stewart, Matthew; Keightley, Alexander; Maguire, Anne; Chadwick, Barbara; Vale, Luke; Homer, Tara; Douglas, Gail; Deery, Chris; Marshman, Zoe; Ryan, Vicky; Innes, Nicola; ,
The management of carious primary teeth is a challenge for patients, parents and clinicians. Most evidence supporting different management strategies originates from a specialist setting and therefore its relevance to the primary care setting is questionable. The UK National Institute for Health Research (NIHR) Health Technology Assessment (HTA) has commissioned the FiCTION (Filling Children's Teeth: Indicated Or Not?) trial; a multi-centre primary dental care randomised controlled trial (RCT) to determine the most clinically and cost-effective approach to managing caries in the primary dentition in the UK. This large trial began in 2012, is due to be completed in late 2017 and involves 72 practices and 1, 124 children initially aged three to seven years with dentine caries, following randomisation to one of three caries management strategies. Clinical, radiographic, quality of life, treatment acceptability and health economics data are collected during the three-year follow up period. This article provides an overview of the development and conduct of FiCTION and discusses some approaches adopted to manage challenges and achieve the patient recruitment target.